Natureza morta, de Susana de Sousa Dias: políticas e ritornelos da imagem - Guideroli, Ilma Carla Zarotti [UNIFESP] (2020)
This study consists of an analysis of the film Still Life (2005), by Portuguese filmmaker and artist Susana de Sousa Dias, who carried out extensive research on the documentary collections of the Salazar dictatorship (1926-1974) in order to produce it. We are interested in investigating it with a view to proposing relationships according to the following guiding axes: the problem of the archive, the faces and portraits of identification of political prisoners, the montage procedures and the issue of gestures. For that, we will use the reflections of a group of authors, including Didi-Huberman, Foucault, Deleuze and Guattari. The last two, in particular, provide us with the relevant notion of refrain, with which our text maintains an intense dialogue, since, by showing the movement of images and sounds in continuous rearrangements, it helps us to illuminate and to think singularities of the montage, which is an important goal of the work. The clearest effects of these procedures have an obvious political aim: the images can acquire other senses, presenting virtually deeper layers, leading them to something like a turning point, in such a way that new narratives can be presented, beyond those based on official history. It should also be said that, rather than explicitly applying theoretical references as instruments for analysis, the purpose was to establish dialogues and possible connections between them, also valuing the understanding of the images of the film itself, as an event and thought of its own.